Oral Priming with Replicating Adenovirus Serotype 4 Followed by Subunit H5N1 Vaccine Boost Promotes Antibody Affinity Maturation and Expands H5N1 Cross-Clade Neutralization - Khurana, Surender; Coyle, Elizabeth M.; Manischewitz, Jody; King, Lisa R.; Ishioka, Glenn; Alexander, Jeff; Smith, Jon; Gurwith, Marc; Golding, Hana (PloS one, 2015)
A Phase I trial conducted in 2009-2010 demonstrated that oral vaccination with a replication competent Ad4-H5 (A/Vietnam) vector with dosages ranging from 107-1011 viral particles was well tolerated. HA-specific T-cell responses were efficiently induced, but very limited hemagglutination-inhibiting (HI) humoral responses were measured. However, a single boost of Ad4-H5-Vtn vaccinated individuals with a unadjuvanted licensed H5N1 (A/Vietnam) subunit vaccine resulted in superior HI titers compared with unprimed subjects. In the current study, the impact of Ad4-H5 priming on the quality of the polyclonal humoral immune response was evaluated using a real-time kinetics assay by surface plasmon resonance (SPR). Total binding of serum polyclonal antibodies from the Ad4-H5-Vtn primed groups against both homologous H5N1-A/Vietnam/1194/2004 (clade 1) and heterologous A/Indonesia-5/2005 (clade 2.1) HA1 head domain was significantly higher compared with sera from individuals that received subunit H5N1 vaccination alone. SPR measurements also demonstrated that the antigen-antibody complex dissociation rates (a surrogate for antibody affinity) of serum antibodies against the HA1 of H5N1-A/Vietnam were significantly higher in the Ad4-H5 primed groups compared with those from the unprimed group. Furthermore, strong correlations were observed between the antibody affinities for HA1 (but not HA2) and the virus neutralization titers against the homologous strain and a panel of heterologous clade 2 H5N1 strains. These findings support the concept of oral prime-boost vaccine approaches against pandemic influenza to elicit long-term memory B cells with high affinity capable of rapid response to variant pandemic viruses likely to emerge and adapt to human transmissions.